2013
DOI: 10.1149/05002.1583ecst
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nanosheet Size on Activity and Durability of RuO2 Nanosheet Pt/C Catalyst

Abstract: Composite catalyst (RuO2ns-Pt/C) composed of commercial carbon supported Pt (Pt/C) and various size RuO2 nanosheets (RuO2ns) were synthesized.The improvement in ORR activity and durability of the different catalysts has been evaluated and is discussed as a function of the size of RuO2ns. The RuO2ns size was found to greatly influence the catalytic properties with smaller RuO2ns giving better performance than larger ones. Composite catalyst with small sized RuO2ns exhibit initial activity 2 times higher than Pt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
16
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 13 publications
1
16
0
Order By: Relevance
“…31 In an earlier study, it was shown that the durability of commercial Pt/C (20 mass% of Pt) with ultrasmall Pt (1-1.5 nm) could be improved without sacrificing initial activity.…”
mentioning
confidence: 99%
“…31 In an earlier study, it was shown that the durability of commercial Pt/C (20 mass% of Pt) with ultrasmall Pt (1-1.5 nm) could be improved without sacrificing initial activity.…”
mentioning
confidence: 99%
“…We consider that the ORR activity shown by the reduced Pt nanoparticles on nanosheet contributes to the higher ORR activity retention rate in practical catalyst. As discussed in our previous papers, [10][11][12] RuO 2 nanosheet modified Pt/C electrocatalyst shows enhanced durability compared to non-modified Pt/C. Certainly, the degradation rate of carbon blacks used in practical catalysts and HOPG used in this model electrode study should be quite different due to the difference in degree of graphitization.…”
Section: Resultsmentioning
confidence: 79%
“…We have recently shown that the durability of commercial Pt supported on carbon black can be enhanced with the addition of RuO 2 nanosheet. 17,18 Model electrode studies have elucidated that there is a strong electrostatic interaction between RuO 2 nanosheets and dissolved Pt ions derived electrochemically.19 This strong electrostatic interaction between ionic Pt species in solution and the nanosheets is considered to decrease the loss of dissolved Pt species into electrolyte due to migration.In this study, we present experimental evidence of a strong metalsupport interaction between RuO 2 nanosheet and metallic Pt, which may be another reason for the enhanced durability of RuO 2 nanosheet modified Pt/C. A model electrode system was employed to evaluate the difference in the adsorption strength of metallic Pt on RuO 2 nanosheet and carbon surfaces.…”
mentioning
confidence: 99%
“…We have recently shown that the durability of commercial Pt supported on carbon black can be enhanced with the addition of RuO 2 nanosheet. 17,18 Model electrode studies have elucidated that there is a strong electrostatic interaction between RuO 2 nanosheets and dissolved Pt ions derived electrochemically.…”
mentioning
confidence: 99%
See 1 more Smart Citation